Biocomposites reinforced with natural fibers: 2000-2010 - Faruk, O.; Bledzki, A. K.; Fink, H. P.; Sain, M.
Due to environment and sustainability issues, this century has witnessed remarkable achievements in green technology in the field of materials science through the development of biocomposites. The development of high-performance materials made from natural resources is increasing worldwide. The greatest challenge in working with natural fiber reinforced plastic composites is their large variation in properties and characteristics. A biocomposite's properties are influenced by a number of variables, including the fiber type, environmental conditions (where the plant fibers are sourced), processing methods, and any modification of the fiber. It is also known that recently there has been a surge of interest in the industrial applications of composites containing biofibers reinforced with biopolymers. Biopolymers have seen a tremendous increase in use as a matrix for biofiber reinforced composites. A comprehensive review of literature (from 2000 to 2010)on the mostly readily utilized natural fibers and biopolymers is presented in this paper. The overall characteristics of reinforcing fibers used in biocomposites, including source, type, structure, composition, as well as mechanical properties, will be reviewed. Moreover, the modification methods; physical (corona and plasma treatment)and chemical (silane, alkaline, acetylation, maleated coupling, and enzyme treatment)will be discussed. The most popular matrices in biofiber reinforced composites based on petrochemical and renewable resources will also be addressed. The wide variety of biocomposite processing techniques as well as the factors (moisture content, fiber type and content, coupling agents and their influence on composites properties)affecting these processes will be discussed. Prior to the processing of biocomposites, semi-finished product manufacturing is also vital, which will be illustrated. Processing technologies for biofiber reinforced composites will be discussed based on thermoplastic matrices (compression molding, extrusion, injection molding, LFT-D-method, and thermoforming), and thermosets (resin transfer molding, sheet molding compound). Other implemented processes, i.e., thermoset compression molding and pultrusion and their influence on mechanical performance (tensile, flexural and impact properties)will also be evaluated. Finally, the review will conclude with recent developments and future trends of biocomposites as well as key issues that need to be addressed and resolved.
Keywords: BIOCOMPOSITES; NATURAL FIBER; BIOPOLYMER; NANOFIBER; ACETYLATION; ALKYLATION; SILANE; MALEATED COUPLING; ENZYME TREATMENT; THERMOPLASTIC; THERMOSETS; INJECTION MOLDING; COMPRESSION MOLDING; EXTRUSION; PULTRUSION; PULTRUSION; SHEET MOLDING COMPOUND; LFT-D METHOD; TENSILE; FLEXURAL; IMPACT